A Case of Metastatic Bladder Cancer in Both Lungs Treated with Korean Medicine Therapy Alone - Lee, Dong-Hyun (S. Karger AG, 2014)
This case report is aimed to investigate the effects of Korean medicine therapy (KMT) including oral herbal medicine and herb nebulizer therapy in treating metastatic bladder cancer in the lungs. A 74-year-old man was diagnosed with metastatic bladder cancer in both lungs in August 2013. He refused any chemotherapy and was admitted to our hospital in a much progressed state on January 11, 2014. Since then, he was treated with KMT until May 17, 2014. The main oral herbal medicines were Hyunamdan made of heat-processed ginseng, Hangamdan S made of Cordyceps militaris, Panax ginseng radix, Commiphora myrrha, calculus bovis, margarita, Boswellia carteri, Panax notoginseng radix and Cremastra appendiculata tuber, and nebulizer therapy with Soram nebulizer solution made of wild ginseng and Cordyceps sinensis distillate. Their effect was evaluated considering the change of the main symptoms and using serial chest X-ray. The size and number of multiple metastatic nodules in both lungs were markedly decreased and the symptoms had disappeared. These results suggest that KMT can be an effective method to treat metastatic bladder cancer in the lungs.